Self-Regulation Of The Qur'an Reciters Student - Nelly Marhayati; Pasmah Chandra; Ayu Indah Lestari (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2021)
The purpose of this study was to find out how the process of self-regulation of Qur'an reciters tutors at Ma'had al-Jami'ah IAIN Bengkulu. This research used descriptive qualitative method by involving 12 student as respondens who have completed memorizing more than 5 Juz and are currently in 5th and 7th semsester. Data collected through interviews, observation, and documentation. It was found that two factors form self-regulation of Qur'an reciter students. Internal factors are self-observation, judgmental process, and self-response. The external factor is support from a closed family. In addition, there are supporting and inhibiting factors in the self-regulation process. Supporting factors in the form of an intention to memorize, have a memorizing target, and strong motivation and support from the closest people. The inhibiting factors are laziness, finding difficult vocabulary, gadgets, and negative mood disorders.